Pengaruh Jumlah Sudu dan Pembebanan Terhadap Energi Listrik Yang Dihasilkan OlehTurbin Angin SumbuHorizontal Skala Mikro - Vita Ayu Aspriyanti; Herman Saputro; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
The needs of electrical energy particularly in Indonesia is very great and continues to increase every year. The development of a micro scale horizontal axis wind turbine can be a solution to solve that. This research has a purpose to find out the influence of number of blades and wind speed variation on electrical energy produced by micro scale horizontal axis wind turbines. The method which was used in this research was experiment method and it was implemented at the Laboratory of Study Program of Mechanical Engineering Education of Sebelas Maret University. The variable that was used in this research was by using blades with airfoil SG6043 with variations of blades number and the giving load in the form of 12v and 24v LED lights. The horizontal axis wind turbine rotor has a diameter of 800 mm and a blade length of 400 mm which is printed with 3D Printing PLA material. The data collection was implemented on the wind speed of 1 m/s to 5 m/s. The results of this research is the wind turbine that used 5 blades produced the highest power of 9.22 Watt at 24v loading and had the highest power performance value of 0.241 at maximum wind speed of 5 m/s. The number of blades and wind speed and loading could affect the electrical power produced by the turbine, the more blades and the higher the wind speed, the greater the power generated by the turbine.